Eksposisi Kolose 2: 6-8: Generasi Z Yang Terpapar Sindrom Fear of Missing Out - Pasaribu, Ferdinan (Sekolah Tinggi Teologi Sriwijaya, 2024)
The aim of this article is to provide a theological alternative for resolving the phenomenon of Fear of Missing out syndrome. Fear of Missing out Syndrome results in psychological problems, consumerism, materialism, impaired concentration or focus (excessive social media trends) and negative emotions due to gadget use. The author understands this problem by examining the theological principles in the text Colossians 2: 6-8. The theological principle is the Bible as the basis, foundation, foundation of all life. This means that God is the center of the Christian framework of thought in all aspects of Christianity. The author uses a literature review approach from various sources, as well as hermeneutic analysis to study the text of Colossians 2: 6-8. As a result of the research, the author found that in the text Colossians 2: 6-8, it provides a theological solution for the zoomer generation who are exposed to the Fear of Missing syndrome, that the main thing in the Christian life is accepting Jesus Christ. The Lord Jesus is the source of life, the source of everything humans need and is able to provide satisfaction in all aspects of human life. Second, removed, wake up in Christ and live in thanksgiving. The zoomer generation and humans will be stronger and stronger in facing life's challenges, especially the trend that faces humans by building their lives in the Lord Jesus Christ.